2017
DOI: 10.1111/mec.14348
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 diversification and hostplant utilization patterns in specialist and generalist moths: Birth, death and adaptation

Abstract: Across insect genomes, the size of the cytochrome P450 monooxygenase (CYP) gene superfamily varies widely. CYPome size variation has been attributed to reciprocal adaptive radiations in insect detoxification genes in response to plant biosynthetic gene radiations driven by co-evolution between herbivores and their chemically defended hostplants. Alternatively, variation in CYPome size may be due to random "birth-and-death" processes, whereby exponential increase via gene duplications is limited by random decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 67 publications
(86 reference statements)
3
64
1
Order By: Relevance
“…Genomic comparisons among anciently evolved herbivores and distantly related non-herbivores, or across herbivorous lineages, have uncovered striking expansions and losses of genes involved in chemosensation and detoxification in arthropods (e.g., (19,32,65,69,70) . Yet the lack of dense sampling among closely related taxa has, in many cases, precluded pinpointing the timing of these changes relative to the evolution of herbivory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic comparisons among anciently evolved herbivores and distantly related non-herbivores, or across herbivorous lineages, have uncovered striking expansions and losses of genes involved in chemosensation and detoxification in arthropods (e.g., (19,32,65,69,70) . Yet the lack of dense sampling among closely related taxa has, in many cases, precluded pinpointing the timing of these changes relative to the evolution of herbivory.…”
Section: Discussionmentioning
confidence: 99%
“…However, new studies suggest that this finding obscures potentially adaptive "blooms" that are more nuanced, localized phylogenetically and driven by the particular niches of the insects involved. Specifically, studies on insects with well-defined interactions with plants, including shifts from carnivory to folivory in bees and variation in diet breadth across Drosophila and Lepidoptera species, largely refute a purely stochastic birth-death hypothesis (19,58,(63)(64)(65) . We found a similar pattern of fewer CYP450 gene numbers in S. flava , likely due to a narrowing of their dietary niche, coupled with high turnover rates (high gain + loss rate) and a modest, but biologically significant bloom in the canonical xenobiotic resistance gene Cyp6g1 .…”
Section: Gene Blooms Not Gene Family Expansions As a Consequence Ofmentioning
confidence: 99%
“…Webworm larvae express constitutively high levels of CYP6AE1 and CYP6AE89 transcripts irrespective of larval consumption of hostplant flowers or artificial diets amended with xanthotoxin or sphondin (Calla et al, 2017). For this study, gene expression levels of CYP6AE1 and CYP6AE89 were evaluated in midguts of caterpillars consuming the linear furanocoumarin xanthotoxin or the angular furanocoumarin sphondin.…”
Section: Differential Expression Of P450smentioning
confidence: 99%
“…A genome‐wide analysis of cytochrome P450s in the parsnip webworm identified, amongst others, transcripts of eight previously undescribed CYP6AE enzymes in the genome (CYP6AE89, CYP6AE90, CYP6AE91, CYP6AE92, CYP6AE93, CYP6AE95, CYP6AE96 and CYP6AE127) and confirmed the presence of CYP6AE1 reported earlier (Li et al ., ). Of these, CYP6AE1, CYP6AE89, CYP6AE91, CYP6AE93 and CYP6AE95 were found in the whole‐larva transcriptome, with two transcripts – CYP6AE1 and CYP6AE89 – expressed constitutively at very high levels (Calla et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Seminal work on insects revealed that a generalist insect has more detoxification enzymes with lower catalytic activity towards a wider variety of substrates than a specialist (Li, Baudry, Berenbaum, & Schuler, ; Li, Berenbaum, & Schuler, ; Li, Zangerl, Schuler, & Berenbaum, ). Moreover, the diversification of detoxification enzymes in relation to host plants appears adaptive and nonrandom (Calla et al., ). The regulation of cytochrome P450 genes is also consistent with host‐plant specialization in herbivorous Drosophila (Bono, Matzkin, Castrezana, & Markow, ).…”
Section: Introductionmentioning
confidence: 99%